Kahoot and Quizizz Training for Science Teachers in the Online Learning Evaluation Process to Improve Teachers’ Mastery of Technology - Febblina Daryanes; Irda Sayuti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Teachers play a role in planning, implementing, and evaluating the learning process. During online learning, teachers must be able to design online learning that is effective, efficient, innovative, and interesting. Based on interviews with teachers who are members of the Science MGMP SMP in Pekanbaru, information was obtained that the majority of teachers still have difficulty evaluating online learning. According to students carrying out evaluations through WhatsApp groups makes them less motivated. This service activity aims to improve teachers’ mastery of technology in using the Kahoot and Quizizz applications as an evaluation system during online learning and fostering creative and innovative attitudes. The method in community service activities is through training and technical guidance which is carried out through face-to-face and online mentoring. Participants were given a pretest and posttest questions to see the achievement of material content and were given assignments. It is known that the average pretest score of the trainees is 61.58, and the posttest value of the participants is 91.58. Seen an increase in the value of participants with N-Gain of 0.77, which indicates an increase in the value of participants in the high category. The quality of the outputs of the tasks collected by the participants was also very good. It can be concluded that the service participants have been able to create interactive quizzes based on Kahoot and Quizizz and are able to apply them in the learning process.